Creep and recovery behaviors of magnetorheological elastomer based on polyurethane/epoxy resin IPNs matrix. (4th December 2015) - Qi, S; Yu, M; Fu, J; Li, P D; Zhu, M
Abstract: This paper mainly investigated the creep and recovery behaviors of magnetorheological elastomers (MRE) based on polyurethane/epoxy resin (EP) graft interpenetrating polymer networks (IPNs). The influences of constant stress level, content of EP, particle distribution, magnetic field and temperature on the creep and recovery behaviors were systematically investigated. As expected, results suggested that the presence of IPNs leads to a significant improvement of creep resistance of MRE, and creep and recovery behaviors of MRE were highly dependent on magnetic field and temperature. To further understand its deformation mechanism, several models (i.e., Findley's power law model, Burgers model, and Weibull distribution equation) were used to fit the measured creep and recovery data. Results showed that the modeling of creep and recovery of samples was satisfactorily conducted by using these models. The influences of content of EP and magnetic field on fitting parameters were discussed, and relevant physical mechanism was proposed to explain it qualitatively.